A quality systems study on Storck Products, Inc. - Basiao, Yazmin; Luna, Eileen P.; Samson, Kristine C. (Diliman, Quezon City College of Engineering, 2000)
Storck Products, Inc. is just one of the established manufacturing companies in the country. It produces hard candies, soft candies, and bubble gums. One of its popular products is the Storck Eucalyptus Mentho Candy which is the product chosen for this study because of its big contribution to the company's sales performance. In order to gather data, plant visits and interviews were conducted. After documenting the product and the process, Statistical Process Control (SPC) tools were used to perform the analysis. It was found that defective candies are being produced and that incorrect shape and size and the presence of cracks on the candies contribute a lot to this problem. The Fraction Nonconforming Control Chart with variable sample size was used and the Sensitizing Rules were applied to determine if the process is out of control. Defective candies produced was identified as the main problem. Causes of these were determined and analyzed and it was found out that the main problem. Causes of these were determined and analyzed and it was found out that the main contributor to the production of defective candies is machine trouble. Alternatives were generated that would help solve the main problem and the gorup came up with the final recommendation of continuing the use of the old and currently used machines for operation since it is more economical to do so than purchase new machines but there should be improved maintenance to these machines and more advanced ways of repairing.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 135 : Industrial Quality Control
Keywords: Storck Products Incorporated; Candy industry; Quality control